Analisis Performa Ion Thruster Dengan Variasi Jarak - andri, Andriawan; Putra, Ikbal Rizki; Andriawan (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
This research aims to examine the performance of ion thrusters with varying distances. An ion thruster is an electric propulsion technology that generates thrust by expelling positively charged ions. This technology offers high fuel efficiency, which is crucial for space missions that require minimal fuel endurance. The study uses a prototype ion thruster in a laboratory setting with a testing voltage of 5V. The testing focuses on analyzing current strength as a primary performance parameter. The research results are expected to provide insights into optimizing energy use for spacecraft, enabling fuel load reduction and increased payload capacity. This study also contributes to the sustainable development of space technology by emphasizing the importance of efficient energy consumption in ion thruster operations. The research employs an experimental method by measuring the performance of ion thrusters at various distances. The results of this study are expected to serve as a reference for further development of ion thruster technology, particularly in the aspects of energy conservation and operational efficiency enhancement